Screen-Printed, Pure Carbon-Black Thermocouple Fabrication and Seebeck Coefficients - Christina Offenzeller; Marcel Knoll; Bernhard Jakoby; Wolfgang Hilber (Sensors, 2019)
Thermocouples classically consist of two metals or semiconductor components that are joined at one end, where temperature is measured. Carbon black is a low-cost semiconductor with a Seebeck coefficient that depends on the structure of the carbon particles. Different carbon black screen-printing inks generally exhibit different Seebeck coefficients, and two can therefore be combined to realize a thermocouple. In this work, we used a set of four different commercially available carbon-black screen-printing inks to print all-carbon-black thermocouples. The outputs of these thermocouples were characterized and their Seebeck coefficients determined. We found that the outputs of pure carbon-black thermocouples are reasonably stable, linear, and quantitatively comparable to those of commercially available R- or S-type thermocouples. It is thus possible to fabricate thermocouples by an easily scalable, cost-efficient process that combines two low-cost materials.